Evaluation of a compressed air foam system to clean quail rearing facilities - Jill Wright Skrobarczyk; David James Caldwell; Kenneth Scott McKenzie; Ashley Charles Blankenburg; James Allen Byrd; Morgan Brian Farnell (Journal of Applied Poultry Research)
SUMMARY: An effective cleaning and sanitation protocol is important to mitigate disease outbreaks in poultry rearing facilities. This is especially important in cases of salmonellosis where there is a risk of disease transmission to humans. Compressed air foam systems (CAFS) may serve as an alternative carrier for foaming agents to clean and sanitize agricultural surfaces following an outbreak. The objective of this study was to evaluate the effects of a CAFS applied commercial firefighting foam (FF) and chlorine-based foaming cleaner (FC) in floor pen and caged quail rearing facilities with a history of salmonellosis. A firefighting foam concentrate (Phos-Chek WD881) and foaming cleaner (Chlor-A-Foam XL) were diluted in water and applied to floor pen and caged rearing facilities using a compressed air foam system. Total aerobes and cellular adenosine triphosphate (ATP) were quantified pre- and post-treatment using swabs. Both treatments significantly reduced aerobic bacteria in the floor pen and caged quail facilities (P < 0.05). The greatest reduction of 1.74 log10 CFU/mL was reported in the floor pen facility following FC treatment. Microbial ATP levels were also significantly reduced by both the CAFS applied FF and the FC in the floor pen and caged quail facilities (P < 0.05). Treatment of floor pen facilities with the FF resulted in the greatest ATP reduction of 4,201 RLU. These data summarize the efficacy of CAFS applied foaming agents suggesting that a compressed air foam system may serve as a practical method to clean quail rearing facilities.